Study on the relationship between ecological spatial network structure and regional carbon use Efficiency: A case study of the Wuding river basin - Yufan Zeng; Xiang Chen; Ziyan Yang; Qiang Yu (Ecological Indicators, 2023)
Plant carbon use efficiency (CUE) reflects the carbon assimilation ability and carbon sequestration potential of organisms, and is an important quantitative index in ecology. Therefore, investigating CUE can better understand and explore ecosystem carbon flux and carbon allocation patterns. In this paper, the Wuding River Basin is taken as the research area. MODIS were used to calculate CUE and explore its spatiotemporal variations. Using remote sensing environmental indicators (RSEI) extract ecological sources, and the MCR model were used to construct an ecological spatial network. By analogy with complex network theory, calculate topological indicators, and combine its ecological significance to investigate the relationship between CUE and these indicators, considering their ecological significance. The results are as follows: (1) The average CUE value slightly increased, with an overall increase in the southeastern part of the study area, minor changes in the southern parts, and an overall decrease in the western and northern parts of the basin. (2) CUE showed a strong positive correlation with closeness centrality, betweenness centrality, harmonic closeness centrality, and a negative correlation with eccentricity, while no significant correlation was found with component number.